Effect of pretreatment with calcium‐containing desensitizer on the dentine bonding of mild self‐etch adhesives. (28th March 2013) - Pei, Dandan; Liu, Siying; Huang, Cui; Du, Xijin; Yang, Hongye; Wang, Yake; Deng, Donglai
Abstract : Desensitizing agents are frequently applied to sensitive teeth and may affect subsequent resin bonding. The current study aimed to evaluate the bonding performance of two self‐etch adhesives containing functional monomers to dentine pretreated with three new calcium‐containing desensitizers. No desensitizer was applied in the control group. Groups 1, 2, and 3 were treated with an arginine–calcium carbonate‐containing polishing paste, a casein phosphopeptide–amorphous calcium phosphate (CPP‐ACP)‐containing paste, and an experimental hydroxyapatite paste, respectively. G‐Bond and Clearfil S 3 Bond were used for bonding after desensitizer treatments. The microtensile bond strength (μTBS) was tested ( n = 20 beams per group) and failure mode distribution was analyzed. Scanning electron microscopy was used to observe the occlusion of dentinal tubules. The mean (±SD) μTBS values, expressed in MPa, of groups 1, 2, and 3 and the control group were, respectively, 30.81 (7.79), 44.41 (8.02), 31.49 (6.13), and 41.40 (8.67) for G‐Bond and 39.63 (9.59), 32.55 (7.86), 37.50 (8.60), 27.90 (6.52) for S3 Bond. Most failures were recorded as adhesive failure (69.375%), instead of cohesive failure or mixed failure. The dentinal tubules were seldom plugged in group 2, but were mostly occluded in groups 1 and 3. Two‐wayanova indicated that desensitizer application in association with a compatible adhesive system should be used when endeavoring to control hypersensitivity without adverse interference in bonding.